Asyut in Modern Times: The Problem of Invisibility. (February 2021) - Gran, Peter
Abstract : If a major city, the major administrative capital of the south and an integral part of how the system reproduces itself, is invisible beyond an occasional passing reference in the familiar narrative of the history of a country, something has gone amiss. Such is the situation of Asyut, a city so invisible that even the English spelling of its name is elusive—variably Asyut, Assuit, Assiut, Siout, or even Essiout—sometimes appearing to be a deliberate attempt to retain an ancient pharaonic or biblical rendering. So why is there this invisibility and how can it be overcome?